First record of the Vulnerable lizard Stenocercus doellojuradoi in the Monte de Sierras and Bolsones ecoregion in Argentina - Valdez Ovallez, Franco M. (2025)
Stenocercus doellojuradoi has been categorized as Vulnerable by the Argentine Herpetological Association, while internationally it has been categorized as Near Threatened by the IUCN. The geographic distribution of this species has always been associated with the Chaco Arid ecoregion. In this work we report for the first time its presence in the Monte de Sierras y Bolsones ecoregion. The new record of S. doellojuradoi extends the distribution of the species in the Province of San Juan by approximately 120 to 145 km in a straight line with respect to previous records in the Valle Fértil Department. Furthermore, this record is of great relevance since it corresponds to the westernmost point of its current known distribution in Argentina.